Tingkat Kebisingan Di Kawasan Permukiman Sekitar PLTD Muara Teweh - Uswatun Hasanah; Zulfikar Ali As; Maharso Maharso (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2016)
Abstract: Level of Noise in the residential around muara teweh’s PLTD. Muara Teweh’s PLTD was one of the regional companied responsible for the provision of electricity serviced. The impact of the operation of the PLTD is the emergence of noise caused by the PLTD engine so that it appeared on public complainted, especially communication disordered, disordered of physiological and psychological disordered. This study aims to determine the noise level and subjective complainted felt in residential areas around Muara Teweh’s PLTD. This research was a descriptive observational describe the noise level in residential areas Muara Teweh’s PLTD. This study include cross-sectional design that aims to determine the noise until at residential areas around Muara Teweh’s PLTD and connect with public complainted in residential areas around Muara Teweh’s PLTD. The measurement resulted show noise levels in residential areas around Muara Teweh’s PLTD exceeded the NAV according KEPMEN / LH / 48/1996, which is 62.9 dBA in the North, 70.4 dBA in the Northeast, 69.3 dBA in the East , 69.4 dBA in the direction of the Southeast, 72.3 dBA in the south, 72.2 dBA in the direction of the Southwest, 78.2 in the West and 75.5 dBA in the northwest. Subjective complainted of the most widely felt in residential areas Muara Teweh’s PLTD form (45.9%), headache (56.8%), discomfort (91.9%), insomnia (83.8%) fast and emotions (40.5%). Efforts should be madeto controlnoise levelsand complaintsaregiving them the toolsnoise suppressioninengine room, thickenthe barrier, put upcurtainsat thewindows of the houseanddo notoftenopen thedoor. Keywords : Noisy environment, residential noise